Pengaruh Kualitas Pelayanan dan Citra Toko Terhadap Loyalitas Pelanggan Di Toko Bona Petshop - Novi Indah Amelia (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
This research aims to obtain empirical evidence regarding the influence of service quality and store image on customer loyalty at Bona Petshop. It is hoped that this research can contribute to the development of management science, especially marketing management which includes service quality, store image and customer loyalty. The data collection used was the Accidental Sampling technique, namely a random or sudden sampling technique by distributing questionnaires to 66 people who were used as research samples conducted in 2022. Data analysis used multiple linear regression and obtained the equation value Y = 1.488 + 0.434 (X1) + 0.391 (X2) and the coefficient of determination of service quality and store image on customer loyalty is 36.6%.